Progresses in the classification and mechanism of methane-oxidizing bacteria - CAI Chaoyang; HE Zhanfei; HU Baolan (浙江大学学报. 农业与生命科学版, 2016)
Methane (CH4) as a colorless, odorless organic gas, is one of the most simple hydrocarbons and is widely distributed in environment. As the second most important greenhouse gas, only following carbon dioxide, methane contributes a lot to the global warming.Methane-oxidizing bacteria are a kind of microorganisms which directly use methane as carbon and energy source. Because they can convert methane into carbon dioxide and mitigate the global greenhouse effect, methane-oxidizing bacteria are attracting more and more attention. Methane-oxidizing bacteria not only reduce methane emissions in the soil, but also uptake the methane in the gas phase of the unsaturated soil. They are important to mitigate the global greenhouse effect.According to whether can uptake oxygen in environment as the electron acceptor or not, methane-oxidizing bacteria can be divided into aerobic and anaerobic methane-oxidizing bacteria. Aerobic methane-oxidizing bacteria are gram-negative bacteria, which use methane as carbon and energy source, have been discovered as early as 1906. Because of the potential value of aerobic methane-oxidizing bacteria in practice production, scientists have made extensive research about them in the past 40 years. At the same time, aerobic methane-oxidizing bacteria can reduce soil methane emissions and uptake methane in the atmosphere, playing an important role in global carbon cycle. Because anaerobic methane-oxidizing bacteria’s doubling time is long, research progress about them is slow.Cellular components of different kinds of methane-oxidizing bacteria are different, and they have different enzymes and C1 metabolic pathways. The center metabolic mechanism of C1 component determines the competition ability of different bacteria in different environments. The main center metabolic mechanism can be divided into three categories: ribulose monophosphate cycle, serine cycle, and the Calvin-Benson-Bassham cycle.